COMPARATIVE STUDY BETWEEN MELAYU BATUBARA LANGUAGE AND BAHASA INDONESIA IN COASTAL AREA - Wardatul Fitria Utami; Riqqah Aprilia Wijaya; Rosita Dongoran (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Batu Bara Malay is one of the varieties of Malay used by the people in the Batu Bara area, North Sumatra, which has significant differences from Indonesian. This study aims to conduct a comparative analysis of the phonemic structure of Batu Bara Malay in the Coast and Indonesian. A qualitative approach was used in this study with a contrastive analysis method to identify similarities and differences in the sound system, including vowel and consonant phonemes, intonation, and the use of word stress between the two languages. Data were collected through interviews with native speakers of both languages to obtain data on the use of sounds contextually and document analysis by analyzing related documents such as language dictionaries, and academic articles to compare the use of the same or similar words between the two. The results of the study show that there are significant differences in the phonetic structure between Batu Bara Malay in the Coast and Indonesian, including vowel phonemes, Batu Bara Malay in the Coast has more variations compared to Indonesian. There are unique variations in each language, for example differences in the pronunciation of several consonants and vowels. Intonation patterns are also different, thus significantly affecting the meaning of sentences. The use of word stress also varies, thus affecting communicative understanding between individuals.